MANAJEMEN KEBUTUHAN INFORMASI DOSEN DALAM MELAKSANAKAN TRI DHARMA PERGURUAN TINGGI (Studi Kasus Pada Jurusan SKI Fakultas Adab IAIN Imam Bonjol Padang) - Nasrul Makdis (UIN Imam Bonjol Padang, 2017)
To run the Tri Dharma of Higher Education, lecturers must at all times be able to access and update information quickly. Thus the lecturer will not miss the latest knowledge and information from students or from the general public. Without mastering information, the lecturer will look passive and